2018
DOI: 10.1038/s41388-018-0402-1
|View full text |Cite
|
Sign up to set email alerts
|

CAB39L elicited an anti-Warburg effect via a LKB1-AMPK-PGC1α axis to inhibit gastric tumorigenesis

Abstract: Metabolic dysfunction is a hallmark of gastric cancer (GC). In this study, we reported the identification of Calcium Binding Protein 39-Like (CAB39L) as a novel regulator of tumor metabolism in GC. CAB39L mRNA was frequently silenced by promoter methylation in GC cell lines and tissues. Functional studies suggested that CAB39L functions as a tumor suppressor, as overexpression of CAB39L elicited suppression of multiple cancer phenotypes both in GC cells and an orthotopic mouse model; whilst its knockdown promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…In addition, Li et al identified the aberrant silencing of Calcium Binding Protein 39-Like (CAB39L) in GC by promoter hypermethylation, and represented an epigenetic mechanism that contributes to metabolic dysregulation and GC development. 89 CAB39L elicited an anti-Warburg effect via a LKB1-AMPK-PGC1α axis to inhibit gastric tumorigenesis, and CAB39L-silenced GC cells exhibited an increased sensitivity to metformin. 89 …”
Section: Metformin’s Anti-tumor Effects On Gastric Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, Li et al identified the aberrant silencing of Calcium Binding Protein 39-Like (CAB39L) in GC by promoter hypermethylation, and represented an epigenetic mechanism that contributes to metabolic dysregulation and GC development. 89 CAB39L elicited an anti-Warburg effect via a LKB1-AMPK-PGC1α axis to inhibit gastric tumorigenesis, and CAB39L-silenced GC cells exhibited an increased sensitivity to metformin. 89 …”
Section: Metformin’s Anti-tumor Effects On Gastric Cancermentioning
confidence: 96%
“… 89 CAB39L elicited an anti-Warburg effect via a LKB1-AMPK-PGC1α axis to inhibit gastric tumorigenesis, and CAB39L-silenced GC cells exhibited an increased sensitivity to metformin. 89 …”
Section: Metformin’s Anti-tumor Effects On Gastric Cancermentioning
confidence: 96%
“…This metabolic change provides most of the building blocks (lactate and glycolytic intermediates) required for tumor progression, despite the presence of oxygen . Therefore, it can be a potential therapeutic strategy by reversing the metabolic pattern or an anti‐Warburg effect . Mounting evidence has shown that Sirtuin‐3 (SIRT3), an NAD‐dependent deacetylase, has a dynamic role in regulating cellular metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the knockout and recovery of PRKAA1 in GC cells and xenograft tumour assays in nude mice demonstrated the role of PRKAA1 in suppressing GC cell growth. Recently, it was also shown that phosphorylation and activation of AMPKα1 suppresses gastric tumourigenesis through the LKB1-AMPK-PGC1α axis 33. Notably, the use of metformin, the activator of AMPK, could reduce the risk of GC,34 but these results remain controversial in observational studies 35.…”
Section: Discussionmentioning
confidence: 99%